Advantages and Challenges of Intellectual Property Rights Related to the Shipbuilding Process - Francisco Torres Pérez; Sara Louredo Casado (Poredbeno Pomorsko Pravo, 2022)
The shipbuilding sector benefits greatly from the technological advances that engineers and shipyards attempt to introduce in vessels. Innovations normally come from the fields of industrial inventions, improvements in construction techniques and the design given to certain pieces of the ships. These developments may be protected through rights belonging to the intellectual property family. However, this protection may turn into an obstacle to international maritime traffic if patent holders in a port State enforce their rights against a vessel that enters that port. To avoid these barriers, the Paris Convention for the Protection of Industrial Property established an exception to the patent right regarding components that are used solely to cover the needs of the vessel (Art. 5ter of the Convention). The exclusion was extended subsequently to industrial designs through European regulation. Moreover, some improvements in vessels do not enter an Intellectual Property (IP) registry (through a patent or a design). Many times, they are kept secret by the shipbuilders. Some of these considerations have been crystallised in the most common international contracting forms regarding the construction of ships that we treat in the second part of this work. Thus, in the paper, we attempt to make a full analysis of the existing legal framework at an international, European and Spanish level, as well as of the most common forms used to shape the shipbuilding contract and process.